Comparative analysis of monocyte-derived dendritic cell phenotype and T cell stimulatory function in patients with acute-on-chronic liver failure with different clinical parameters - Wu, Zhipeng; Shi, Hongbo; Zhang, Lei; Shi, Honglin; Miao, Xingzhong; Chen, Liangjuan; Chen, Yu; Ma, Yingmin (Frontiers in Immunology, 2023)
Background: Acute-on-Chronic Liver Failure (ACLF) patients experience systemic inflammation as well as immune dysfunction and exhaustion. The phenotype and functionality of monocyte-derived dendritic cells in ACLF patients with different clinical parameters have not been elucidated.This study included 37 cases of ACLF, 20 cases of Chronic Hepatitis B (CHB) patients, and 12 healthy controls. Demographic and laboratory parameters were collected from the enrolled patients. Peripheral blood samples were obtained from the participants. Monocyte-derived dendritic cells were induced and cultured, followed by co-culturing with T cells from the patients. Cell surface markers and intracellular markers were analyzed using flow cytometry. The relationship between these markers and clinical parameters was compared.Our study found that ACLF patients had lower expression levels of HLA-DR, CD86, and CD54 on monocyte-derived dendritic cells compared to both CHB patients and healthy controls. IL-4, GM-CSF, and alcohol were found to promote the expression of HLA-DR, CD86, and CD54 on monocyte-derived dendritic cells. In ACLF patients, higher levels of procalcitonin (PCT), lower levels of albumin, Decreased prothrombin activity and deceased patients were associated with lower expression of HLA-DR, CD86, and CD54 on monocyte-derived dendritic cells. Peripheral blood mononuclear cells (PBMCs), after removing adherent cells, were co-cultured with monocyte-derived DC. Our study revealed that patients with infection and low albumin levels exhibited a decreased proportion of T cell subsets within PBMCs. Additionally, these patients' T cells showed lower levels of Ki-67 and interferon-gamma (IFN-γ) production.ACLF patients exhibit varying clinical states, with differences in the phenotype and the ability of monocyte-derived dendritic cells to stimulate T cells. Alcohol can stimulate the maturation of monocyte-derived dendritic cells.